(untitled) (Zoological Archives: An International Journal, 2026)
Rewilding – the passive or active restoration of ecological processes, trophic interactions, and species assemblages toward self-regulating ecosystem states – is increasingly applied in semi-arid Mediterranean and sub-Mediterranean landscapes where agricultural abandonment, overgrazing legacy, and long-term predator depletion have created ecologically degraded but potentially restorable terrain. This study monitored biodiversity, vegetation structure, and ecosystem function responses across 42 rewilding sites in Spain, Portugal, and Greece representing three rewilding strategies – passive rewilding (agricultural abandonment with no active management), large herbivore reintroduction (Bos taurus primitive breeds, Equus ferus caballus, Cervus elaphus), and apex predator facilitation (wolf corridor enhancement, lynx reintroduction support sites) – compared to paired actively managed (conventional extensive livestock) reference sites, over a 5-year monitoring period (2019-2023). Passive rewilding sites showed 24.8 +/- 6.4% higher vertebrate species richness, 38.4 +/- 8.4% higher invertebrate diversity (Shannon H’), and 2.84-fold higher above-ground biomass than paired managed references after 5 years. Large herbivore reintroduction sites showed the greatest soil carbon accumulation rate (+48.4 +/- 8.4 g C/m2/year vs. reference; p < 0.001) and highest scrub heterogeneity index (0.84 +/- 0.08 vs. 0.42 +/- 0.06; p < 0.001), attributed to patchy herbivore grazing creating structural diversity. Apex predator facilitation sites showed 42.4% higher mesocarnivore diversity and significant suppression of overabundant lagomorphs, partially releasing vegetation from rabbit herbivory. A Rewilding Effectiveness Index (REI) combining biodiversity, vegetation, and soil function metrics ranked large herbivore reintroduction as the most cost-effective strategy for rapid ecosystem recovery in the first 5 years.